Do silêncio à vitalidade sociocultural dos Chiquitano do Portal do Encantado - Mato Grosso, Brasil - Cintra, Ema Marta Dunck (2016)
How can an ethnic identity that has been wiped out, numbed, silenced by colonization process be identified? In the case of the Chiquitano in the Portal do Encantado-MT, who had positioned themselves as indigenous people to have the right to remain in their territory, the first strategy was to trigger the mother tongue which had taken refuge in the memory of their elders. Thus, the focus of this thesis is to present how, through “memory bilingualism” , this people could trigger an interactive process of resistance, cultural and political positioning of identity assertion. An identity that those who remembered (the elders) were able to reconstruct, given the common unitary point (belonging) of representation and impulsion to the experience of traditional knowledge. This knowledge, inherited from a common past, provoked/articulated/triggered a fight in view of the hegemony imposed by the settlers and their ways of homogenization of knowledge, culture and life. Hence, based on the results of this study, which entangles decolonial authors and authors who treat the language as discourse, it is possible to state that the Chiquitano, when triggered the mother tongue which was stored in their memory, could reach the dwelling for their being and gradually establish a decolonial process, identifying their identity and their place of belonging. That’s because, collectively, they acted and promoted the interaction of different generations of people. Through reflection, they found themselves, creating themselves and their “new” world. By demanding their own school, they produced science. Giving value to the ancestral knowledge, they defined the curriculum and pedagogic practices. In this way, they recorded their culture, which was dormant in the language memory. They produced an authorial and coping pedagogy. The valorization of their knowledge and their being created the possibilities for fighting the dominant power. Memory bilingualism was the guiding basis for the training of teachers and their pedagogic practices, as well as for the assertion of an identity. Everything together, provided the resurgence of a “being more” (FREIRE, 2014) and led the sociocultural vitalization of the Chiquitano do Brasil in the Portal de Encantado-MT.